Opioid Bowel Dysfunction and Narcotic Bowel Syndrome: A Population-Based Study - Choung, Rok Seon (2009)
OBJECTIVES: Opioid prescription use is increasing. Narcotic bowel syndrome (NBS) refers to chronic abdominal pain aggravated by narcotic use. Despite increasing narcotic use, NBS may be under-recognized. The aim of this study was to assess whether gastrointestinal (GI) symptoms in the community are associated with chronic narcotic use and estimate the likely prevalence of NBS. METHODS: Validated self-report GI symptom questionnaires were mailed to 4,898 randomly selected people in the community. The medical charts of all respondents were reviewed to identify participants who had used narcotics and to determine whether they were taking an opioid for > 5 weeks for the treatment of chronic pain (malignant or nonmalignant). NBS was defined as abdominal pain developing in those taking chronic narcotics. The associations between GI symptoms and chronic narcotics use were assessed using logistic regression analysis. RESULTS: A total of 2,913 respondents returned a completed questionnaire (overall response rate 59%, mean age 62, 52% female); 117 participants (4.1%, 95% confidence interval (CI): 3.3, 4.5) were taking narcotics. Five participants (0.17%; 95% CI: 0.06, 0.40%) met the criteria for NBS. Participants using narcotics had an increased use of laxatives (17 vs. 8% in those not using narcotics, P < 0.05). GI symptom reporting was more common in participants on narcotics, although the adjusted (for age, gender, somatic symptom complaints, and use of laxatives) odds ratios (ORs) were significantly increased only for frequent abdominal pain and stool frequency. CONCLUSIONS: NBS may be relatively uncommon. Those on narcotics report additional GI symptoms (abdominal pain and stool frequency) and use more laxatives.